ANALISIS PENDAPATAN USAHA TANI JAGUNG (ZEA MAYS) DI DESA GOAL KECAMATAN SAHU TIMUR KABUPATEN HALMAHERA BARAT - Suhardi, Suhardi; Suwandi, Suwandi; Damping, Jeffin Kristo (EDUTECH CONSULTANT, 2019)
Corn (Zea Mays) is a very potential plant because in addition to corn kernels as the main product, corn stalks can be used as animal feed ingredients. Farming is a way to allocate existing resources effectively and efficiently to obtain maximum profits. Farming costs consist of fixed costs and variable costs. Farmers' income is obtained from the difference between revenue and total farming costs. The feasibility of farming is measured using Revenue Cost Ratio. Research conducted at the Goal Village in East Sahu District, West Halmahera Regency used a quantitative descriptive method, with a population of 34 corn farmers. The sampling technique uses saturated sampling where all members of the population are used as samples. The research data was obtained from observations, interviews and questionnaires. The results of research on maize farmers in Goal Village, the cost of producing corn (Zea Mays) for a 2nd Ha land area is Rp. 10,153,196, - with an income of Rp. 22,789,365, - and sales profits of Rp. 12,636,169, - and the value of the R / C ratio of 2.25. So that farming carried out in the Goal Village of East Sahu District, West Halmahera Regency is feasible.